2014
DOI: 10.1063/1.4871655
|View full text |Cite
|
Sign up to set email alerts
|

Electro-explosion performance of KNO3-filled carbon nanotubes initiator

Abstract: An energetic initiator was developed by integrating KNO3@CNTs nanoenergetic materials with a Cu thin-film microbridge realized onto a ceramic substrate. The electro-explosion performances, including the voltage and current properties, the electro-explosion time, and the explosive sensitivity, of the initiator under capacitor discharge were investigated. The process of electrical explosion was observed by highspeed photography. The explosive sensitivity was obtained by Bruceton method. The results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The CNT arrays showed excellent electron field emission properties. 202 When KNO 3 /CNTs nEMs were integrated with a CTFM deposited onto a ceramic substrate, the electro-explosion performance was greatly improved. This means that, due to the superior electric and thermal conductivities of CNTs, the enhanced chemical reaction of the KNO 3 / CNTs nEMs is beneficial for the miniaturization of electropyrotechnics.…”
Section: Ems Based On Functionalized Cntsmentioning
confidence: 99%
“…The CNT arrays showed excellent electron field emission properties. 202 When KNO 3 /CNTs nEMs were integrated with a CTFM deposited onto a ceramic substrate, the electro-explosion performance was greatly improved. This means that, due to the superior electric and thermal conductivities of CNTs, the enhanced chemical reaction of the KNO 3 / CNTs nEMs is beneficial for the miniaturization of electropyrotechnics.…”
Section: Ems Based On Functionalized Cntsmentioning
confidence: 99%
“…8 Guo et al replaced copper thin film microbridge electropyrotechnics with CNTs combined with potassium nitrate and found that CNTs initiated the ceramic substrate using lower input energy, making it more sensitive. 9 Collins et al showed decreased ESD sensitivity in Al/CuO with the addition of CNTs. 10 Poper et al researched into this phenomena further and discovered that CNTs increase the flame speed of the Al/CuO along with influencing their electrical properties.…”
Section: Introductionmentioning
confidence: 98%
“…MWNT have excellent thermoplasticity and expansibility, which was shown by flowing high-pressure gases from explosive decomposition of picric acid through the multi-wall nanotube channels [ 18 ]. CNT with inner diameters around 10–20 nm were filled with potassium nitrate (KNO 3 ) by wet chemical method, yielding KNO 3 @CNT nEM, which were integrated with a Cu thin-film microbridge to achieve a micro-electropyrotechnic initiator [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%